Pengaruh Profitabilitas, Ukuran Perusahaan, dan Leverage Terhadap Earnings Management Dengan GCG Sebagai Pemoderasi - Siti Nurhaliza; Mhd Reza Irjaldi Hasibuan; Parapat Gultom (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the influence of profitability, firm size, and leverage on earnings management with Good Corporate Governance (GCG) as a moderating variable in manufacturing companies during 2020. Using purposive sampling method, this study analyzed 72 manufacturing companies listed on the Indonesia Stock Exchange. Earnings management was measured using Discretionary Accruals with Modified Jones Model, while GCG was proxied through the proportion of independent commissioners and institutional ownership. The results show that profitability and firm size have a significant positive effect on earnings management, while leverage has a significant negative effect. GCG effectively moderates the relationship between the three independent variables and earnings management, with the strongest moderating effect on the profitability-earnings management relationship. These findings indicate the importance of strengthening GCG mechanisms in mitigating earnings management practices, especially during the Covid-19 pandemic crisis.